2020
DOI: 10.1177/0040517520957397
|View full text |Cite
|
Sign up to set email alerts
|

Binding and release of odor compounds from textiles: Changing fiber selection for apparel

Abstract: Understanding odor volatiles known to constitute those emanating from the human body and how these interact with textiles is relevant to diverse interested parties because of changing fiber use, a better understanding of apparel life cycles including cleaning and the potential for fiber/textile re-use. This paper extends the application of our proton transfer reaction-mass spectrometry model system on adsorption and release behavior of fiber types typical of next-to-skin uses to include both viscose and other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
2
4
0
Order By: Relevance
“…In another series of studies, the body odor matrix was developed by mixing multiple selected VOCs at an optimized ratio to ensure an adequate detection signal for each. 88 , 89 , 90 The results confirmed the low release of VOCs from cotton and wool, but higher release from polyester, consistent with the earlier findings. 90 The adsorption characteristics of wool, cotton, and polyester fibers varied given the different VOCs selected for analysis in this series of research.…”
Section: Odor Control In Sportswearsupporting
confidence: 89%
See 2 more Smart Citations
“…In another series of studies, the body odor matrix was developed by mixing multiple selected VOCs at an optimized ratio to ensure an adequate detection signal for each. 88 , 89 , 90 The results confirmed the low release of VOCs from cotton and wool, but higher release from polyester, consistent with the earlier findings. 90 The adsorption characteristics of wool, cotton, and polyester fibers varied given the different VOCs selected for analysis in this series of research.…”
Section: Odor Control In Sportswearsupporting
confidence: 89%
“… 86 This technique has been used for odor evaluation of textiles under the condition that the source of VOCs in the gaseous mixture is available from the literature or is already known. 87 , 88 , 89 , 90 Other techniques that have been reported include liquid scintillation counting and infrared (IR)-based spectrometer. The former was used to measure the adhesion/release of 14 C-labeled isovaleric acid, a representative substance of sweat odor, to/from knitted fabrics 91 ; and the latter was utilized to quantify the adsorption/emission of four representative VOCs (acetone, ammonia, acetic acid, and butyric acid) in polyester/wool blend fabrics.…”
Section: Odor Control In Sportswearmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of tobacco 1 School of Textiles and Fashion, Shanghai University of Engineering Science, Shanghai, China smoke and hot pot odor from various fabrics has made some progress in analyzing odor components and the difference between fabrics. [5][6][7][8] Nonetheless, the fabric odor desorption research is minimal. The desorption process is also a dynamic process influenced by odorous molecules, fiber properties, fabric structure, and the external environment.…”
Section: Introductionmentioning
confidence: 99%
“…7,11,12 At the same time, the adsorption behavior of volatile compounds by fabrics is related to the compounds' content, structure, and characteristics, such as polarity and aromaticity. 6,13,14 McQueen has successively investigated the body odor intensity of cotton, wool, and polyester. The results showed that polyester has the highest odor intensity.…”
Section: Introductionmentioning
confidence: 99%